2020
DOI: 10.1016/j.nmni.2020.100772
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of mecA and blaZ genes in methicillin-resistant Staphylococcus aureus associated with vaginitis among pregnant women in Ado-Ekiti, Nigeria

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) is an increasingly prevalent pathogen. We studied the prevalence of MRSA and its association with vaginitis during pregnancy. Bacteriological investigations of high vaginal swabs of 350 healthy pregnant women attending antenatal clinics were carried out. Staphylococci were isolated from high vaginal swabs of 135 of the women. The staphylococcal isolates were resistant to multiple antibiotics. The PCR amplification of DNA of 20 selected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 11 publications
0
11
0
1
Order By: Relevance
“…It was realized that certain PSSIs had shown positive for nuc gene ampli cation. The sequence of primer designed that used for detection of nuc gene was previously reported [24]. As it was previously reported, nuc gene was considered as a genetic marker for identi cation of S. aureus using conventional PCR [92] which is a similar nding to our estimation.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…It was realized that certain PSSIs had shown positive for nuc gene ampli cation. The sequence of primer designed that used for detection of nuc gene was previously reported [24]. As it was previously reported, nuc gene was considered as a genetic marker for identi cation of S. aureus using conventional PCR [92] which is a similar nding to our estimation.…”
Section: Discussionmentioning
confidence: 53%
“…Forward (blaZ-F: tacaactgtaatatcggaggg) and Reverse (blaZ-R: cattacactcttggcggtttc) primers used for ampli cation of blaZ gene for staphylococcus isolates was obtained from Okiki et al [24]. The blaZ ampli cation program was performed under the following conditions: Initial denaturation 95°C for 5min, 37 cycles of 95°C for 30s, 55°C for 30s, 72°C for one minute with a nal extension of 72°C for 10min.…”
Section: Pcr For Ampli Cation Of Antibiotic Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…An observational study conducted in Nigeria in 2020 studied 350 apparently healthy mothers between the ages of 19-43 years attending their antenatal clinic [ 16 ]. One hundred and thirty-five women from this study population were swabbed for high vaginal swabs and showed various forms of staphylococcus of which 56.1% of the samples were MSSA .…”
Section: Reviewmentioning
confidence: 99%
“…It has been shown that Lactobacilli has a role in preventing infections, by its ability to maintain vaginal acidic conditions (PH) and ensure the presence of hydrogen peroxide in the vaginal environment. Furthermore, a recent study on BV pathogenesis reported that Lactobacilli can form a biofilm on the epithelium cells of the vagina that serves as a "scaffold" to which many other bacterial species can adhere in a symbiotic manner and then colonize the vaginal cavity [3]. On the other hand, polymicrobial infection is caused by a decrease in lactobacilli and an increase in pathogenic bacteria, primarily anaerobic or microaerophilic species including Gardnerella spp, Mobiluncus spp, Bacteroide spp, Prevotella species, and Mycoplasma spp.…”
Section: Introductionmentioning
confidence: 99%